PENGEMBANGAN LKPD DISCOVERY LEARNING BERBANTUAN AUGMENTED REALITY PADA MATERI BENTUK MOLEKUL BERDASARKAN TEORI VSEPR - Sakira, Audra; Saputra, Andrian; Lisa Tania; Bayu Saputra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop a Discovery Learning Student Worksheet (LKPD) assisted by Augmented Reality (AR) on molecular geometry based on the Valence Shell Electron Pair Repulsion (VSEPR) theory and to describe its characteristics, validity, and practicality. The study employed a Research and Development (R&D) method using the Borg and Gall model, limited to five stages: research and information collecting, planning, preliminary product development, preliminary field testing, and product revision. The research subjects consisted of five tenth-grade chemistry teachers and 93 tenth-grade students from SMAN 14 Bandar Lampung, SMAN 15 Bandar Lampung, and SMAN 16 Bandar Lampung during the needs analysis stage; three Chemistry Education lecturers from the University of Lampung as expert validators; two chemistry teachers; and 28 students from class X.3 of SMAN 14 Bandar Lampung during the preliminary field testing stage. Data were collected using needs analysis questionnaires, expert validation sheets, and teacher and student response questionnaires, and were analyzed descriptively. The results showed that the developed LKPD integrates the Discovery Learning syntax with three-dimensional molecular geometry visualization through Augmented Reality. Expert validation indicated that the LKPD achieved a very good level of validity and was therefore considered valid. Furthermore, teacher and student responses demonstrated that the LKPD possessed a very high level of practicality and was therefore considered practical. Thus, the Discovery Learning LKPD assisted by Augmented Reality on molecular geometry based on the VSEPR theory meets the criteria of validity and practicality and is suitable for use as instructional material in chemistry learning.